When, How, and Barriers of Palliative Care in Intensive Care Unit: A Scoping Review - Sanny Frisca; Dheni Koerniawan; Ketut Suryani; Vincensius Surani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Palliative and near-death conditions in critical ill patients may occur, either predictable prognosis or acute conditions. Nurses are often unprepared for these care needs, resulting in suboptimal patient care. This study aims to review empirical evidence over the past 10 years regarding when to start, how to apply, and constraints during applying palliative care and end of life (EoL) care in intensive care. This review was conducted using journal database CINAHL, PubMed, Scopus, and WOS and selected article by PRISMA. The findings show EoL care begins when the medical team has assessed and approved by the patient and family including using the referral checklist format from intensive care to EoL care including the resources needed. In addition, during the upbringing process counselling and consultation with the family for any decision-making medical measures, nursing rounds, emotional and spiritual support and touches and hugs for the patient and family, including support for the entire medical team. However, there are also obstacles in the right communication time to families, discussions about death, and improving the competence of nurses through EoL education and training.